African Human Rights Law Reports 2011 - Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2014)
African Human Rights Law Reports 2011 Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria 2014 ISSN: 1812-2418 Pages: 241 Print version: Available Electronic version: Free PDF available